Biscuits, the Dole, and Nodding Donkeys : Texas Politics, 1929-1932. - Brown, Norman D. (University of Texas Press, 2019)
When the venerable historian Norman D. Brown published Hood, Bonnet, and Little Brown Jug in 1984, he earned national acclaim for revealing the audacious tactics at play in Texas politics during the Roaring Twenties, detailing the effects of the Ku Klux Klan, newly enfranchised women, and Prohibition. Shortly before his death in 2015, Brown completed Biscuits, the Dole, and Nodding Donkeys, which picks up just as the Democratic Party was poised for a bruising fight in the 1930 primary. Charting the governorships of Dan Moody, Ross Sterling, Miriam "Ma" Ferguson in her second term, and James V. Allred, this engrossing sequel takes its title from the notion that Texas politicians should give voters what they want ("When you cease to deliver the biscuits they will not be for you any longer," said Jim "Pa" Ferguson) while remaining wary of federal assistance (the dole) in a state where the economy is fueled by oil pump jacks (nodding donkeys). Taking readers to an era when a self-serving group of Texas politicians operated in a system that was closed to anyone outside the state?s white, wealthy echelons, Brown unearths a riveting, little-known history whose impact continues to ripple at the capitol.